Red hot [light emitting diodes]. - Perry, T.S (IEEE spectrum)
Light-emitting diodes are ubiquitous in today's high-tech world. But no matter what their application or color, their origin can be traced to the red LED created in 1962 by Nick Holonyak Jr., the winner of this year's IEEE Medal of Honor. The article describes Holonyak's career and the work which produced the first LED, and shows how his influence permeates the industry today.